2011
DOI: 10.1375/jcas.36.3.120
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration Into the Coping Strategies of Preschoolers: Implications for Professional Practice

Abstract: This study aims to explore the coping strategies of preschoolers, by asking 4-year-old children (N = 46) at an early learning centre in Melbourne to describe their coping strategies when dealing with seven age-appropriate challenging situations. The interviews were recorded, transcribed and thematically analysed. The results indicated that preschoolers could articulate coping strategies that are theoretically clustered into productive and nonproductive coping styles. The capacity to identify a range of coping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 27 publications
2
22
0
3
Order By: Relevance
“…They found that 6‐year‐old children tend to use more primary coping in controllable situations (e.g., separation from a friend, peer difficulty, and school failure) than in less controllable situations (e.g., medical procedures or physical accidents). This finding was replicated in later research with preschoolers (Chalmers, Frydenberg, & Deans, ; Pincus & Friedman, ). Chalmers et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that 6‐year‐old children tend to use more primary coping in controllable situations (e.g., separation from a friend, peer difficulty, and school failure) than in less controllable situations (e.g., medical procedures or physical accidents). This finding was replicated in later research with preschoolers (Chalmers, Frydenberg, & Deans, ; Pincus & Friedman, ). Chalmers et al.…”
Section: Introductionmentioning
confidence: 99%
“…Chalmers et al. () found that situations in which preschoolers generated most primary‐control coping strategies included ‘being left out of a game’, ‘choosing between friends’, and ‘choosing between things that the child doesn't like’ as opposed to situations in which secondary control predominated such as ‘night fears’ and ‘being told off by the teacher’. Thus, it appears that preschoolers were able to discriminate between situations and differentially utilise coping strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Chalmers, E. Frydenberg and J. Deans (2011) established what strategies are applied for coping with stress by four year old children while separating from parents, in their relations with friends, teachers, when they dislike something, when they have to make a choice or encounter any night fears. Children cope with stress through play, doing something pleasant, dealing with emerging problems in accordance with their capabilities, applying calming techniques, ignoring problems and searching for help or comfort.…”
Section: Theoretical Substantiation Of Efficiency Of Early Preventionmentioning
confidence: 99%
“…Emotional regulation and coping with stress require children to analyse reasons behind emotions and to show awareness regarding the influence of one's thoughts, beliefs and wills on own behaviours (Chalmers, Frydenberg & Deans, 2011;Mayr & Ulich, 1999;Mayr & Ulich, 2009). When confronted with a stressful event, children who have superior coping skills try to evaluate it cognitively and then show appropriate coping behaviours instead of rapid, sudden and situational reactions (Compas, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When confronted with a stressful event, children who have superior coping skills try to evaluate it cognitively and then show appropriate coping behaviours instead of rapid, sudden and situational reactions (Compas, 2009). During cognitive evaluation of stressful event, these children care the importance and effect of unpleasant situation for their well-being (Chalmers, Frydenberg & Deans, 2011). Children who get high scores from this factor can participate in social environments even when they are under stress.…”
Section: Introductionmentioning
confidence: 99%